UNVEILING THE KEY PERFORMANCE INDICATORS OF SMALL AND MEDIUM-SIZED ENTERPRISES IN THE FOOD INDUSTRY: A COMPREHENSIVE REVIEW - Hanna, A.; Rajkumar, A. Dunstan (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
Small and medium-sized enterprises (SMEs) play a vital role in the global economy, particularly in the dynamic and competitive food industry. Various internal and external factors impact the success and longevity of food-based SMEs, making it essential to identify and understand these critical elements. Despite extensive research on SMEs across different sectors, there is a lack of studies focused explicitly on food-based SMEs. This research seeks to address this knowledge gap by exploring the factors influencing food SME performance through a bibliometric analysis to uncover emerging trends, research gaps, and key growth drivers. The study employs a bibliometric approach to analyze a broad range of academic literature, highlighting influential journals, leading authors, regional research trends, and performance metrics contributing to understanding food SMEs’ success. Key performance indicators include innovation, sustainability, lean operations, entrepreneurial dimensions, market orientation, value co-creation, service quality, quality management, value chain, and organizational effectiveness. These factors help food SMEs navigate market complexities, adapt to changing consumer preferences, and enhance their competitiveness. The study also includes a systematic review of the 30 most-cited articles to assess factors shaping SME success critically. The research underscores the importance of operational efficiency and the need for SMEs to implement lean strategies to maintain agility and resource efficiency. This study contributes to a more comprehensive understanding of the factors driving food SME growth and performance, addressing critical research gaps and fostering a more resilient ecosystem for food-based enterprises to thrive in the global marketplace effectively. JEL Classification Codes: M1, M2, L1, L2, L6.